Renovar el discurso religioso islámico: Entre la crítica, la ética y los desafíos de la era digital - Mekki Klaina (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study examines the renewal of religious discourse in the contemporary Islamic context through a critical and synthetic perspective, employing a descriptive–analytical and comparative methodology that goes beyond mere exposition to include evaluation and the formulation of a constructive framework. The research shows that renewal does not entail a break with tradition but rather an epistemological and institutional process that reactivates ijtihād in light of the maqāṣid (objectives) of the sharīʿa, addressing civilizational and digital challenges without compromising revealed principles. The analysis identifies three interrelated axes: the scientific and ijtihād-based dimension, oriented toward institutional ijtihād in areas such as environmental ethics, artificial intelligence, and bioethics; the media and communicative dimension, which combines theological competence with digital literacy through governance and verification policies; and the educational and social dimension, which promotes critical thinking and media awareness. Overall, authentic renewal emerges as a critical and constructive act that harmonizes knowledge, ijtihād, and responsible communication, reaffirming Islam’s role as a force for justice, knowledge, and dignity in the contemporary world.